2006
DOI: 10.1101/lm.126306
|View full text |Cite
|
Sign up to set email alerts
|

5-HT1a receptor antagonists block perforant path-dentate LTP induced in novel, but not familiar, environments

Abstract: Numerous studies suggest roles for monoamines in modulating long-term potentiation (LTP). Previously, we reported that both induction and maintenance of perforant path-dentate gyrus LTP is enhanced when induced while animals explore novel environments. Here we investigate the contribution of serotonin and 5-HT1a receptors to the novelty-mediated enhancement of LTP. In freely moving animals, systemic administration of the selective 5-HT1a antagonist WAY-100635 (WAY) attenuated LTP in a dose-dependent manner whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
2
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 59 publications
4
31
2
2
Order By: Relevance
“…Moreover, we confirmed the lack of effect of lower doses of 8-OH-DPAt on the slope of the fEPSPs when systemically applied (Levkovitz and Segal 1997). However, it has to be noted that local application of 10 nmol of 8-OH-DPAt in DG produced a reduction of about 50 % in the slope 30 min after its application and a biphasical effect of pSpike amplitudes with a long-lasting decrease (Sanberg et al 2006). Under our conditions, since that synaptic excitability is only slightly diminished in rats treated with a high dose of the drug, the likelihood that a cell will generate an action potential from a given synaptic drive remained unchanged (Fig.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Moreover, we confirmed the lack of effect of lower doses of 8-OH-DPAt on the slope of the fEPSPs when systemically applied (Levkovitz and Segal 1997). However, it has to be noted that local application of 10 nmol of 8-OH-DPAt in DG produced a reduction of about 50 % in the slope 30 min after its application and a biphasical effect of pSpike amplitudes with a long-lasting decrease (Sanberg et al 2006). Under our conditions, since that synaptic excitability is only slightly diminished in rats treated with a high dose of the drug, the likelihood that a cell will generate an action potential from a given synaptic drive remained unchanged (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…In a previous in vivo study, intra hippocampal application of 8-OH-DPAt abolishes inhibition of the population spike observed in the second evoked response at intervals of 30-100 ms (Sanberg et al 2006). In the present study, however, we observed different changes in paired-pulse relationships induced by its systemic administration.…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations